Ways To Effectively Use Investments In Textile Industry Enterprises - Muxtarov Maxmudjon Marifovich (Zien Journals, 2025)
This article analyzes the priority areas of effective use of investments in textile industry enterprises. The optimal mechanisms for placing investment resources are considered based on the specifics of the industry, the technological level of production and the efficiency of using existing production funds. The article also evaluates factors such as the implementation of innovative projects, increasing the profitability of capital investments, and digitization of investment processes as important factors based on foreign experience. Based on the analysis, proposals and recommendations have been developed to increase the economic efficiency of investments in the textile industry.
Keywords: industry; investments; efficiency